PROCESSOS DE SELEÇÃO DOS DIRIGENTES POLÍTICOS NA SECCIONAL MARANHENSE DA ORDEM DOS ADVOGADOS DO BRASIL – OAB/MA: recursos sociais, coalizões e clivagens (1983-2015) - MEIRELES, Samário José Lima (2017)
In this research are analyzed the processes of selection of political leaders of the maranhense branch of the Brazilian bar association, with emphasis on the period between 1983 and 2015. The investigation focused on fourteen elective disputes through which the boards of directors of the entity were chosen. In the operationalization of the study, we sought to apprehend chains of leaders-followers who competed within the institution, evidencing the flows of entries, exits, approximations and distancing. In order to do so, the trajectories of the main protagonists (egos of networks) who competed for positions of direction of the OAB/MA were reconstituted, as well as the clicks of leaders who were formed in these clashes and the cleavages constructed by means of constant realignments in the alliances. Therefore, firstly, the resources accumulated by the agents that stood out in these disputes were identified, and secondly, the networks of relations (through the use of the UCINET and NETDRAW programs) constituted and activated for electoral purposes, also seeking to reveal the social bases of interconnections, ties and links more or less ephemeral.